Construction and Regulation of Polymer@Silica Microspheres with Double-Shell Hollow Structures - Mingxiu Jiang; Yuanyuan Yang; Jiawei Feng; Zhaopan Wang; Wei Deng (Molecules)
Microspheres with well-defined hollow structures have been attracting interest due to their unique morphology and fascinating properties. Herein, a strategy for morphology and size control of hollow polymer@silica microspheres is proposed. Multilayer core–shell polymer microspheres, containing substantial carboxyl groups inside, evolve into microspheres with a 304 nm hollow structure after alkali treatment, which are used to construct hollow polymer@silica microspheres by coating the inorganic layer using the layer-by-layer (LBL) and sol–gel methods, respectively. The inorganic shell thickness of hollow polymer@silica microspheres can be adjusted from 15 nm to 33 nm by the self-assembled layers in the LBL method and from 15 nm to 63 nm by the dosage of precursor in the sol–gel method. Compared to the LBL method, the hollow polymer@silica microspheres prepared via the sol–gel method have a uniform and dense inorganic shell, thus ensuring the complete spherical morphology of the microspheres after calcination, even if the inorganic shell thickness is only 15 nm. Moreover, the hollow polymer@silica microspheres prepared via the sol–gel method exhibit improved compression resistance and good opacity, remaining intact at 16,000 psi and providing the corresponding coating with transmittance lower than 35.1%. This work highlights the morphology regulation of microspheres prepared by different methods and provides useful insights for the design of composites microspheres with controllable structures.